2020
DOI: 10.1002/dac.4538
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid elephant herding optimization and cultural algorithm for energy‐balanced cluster head selection scheme to extend the lifetime in WSNs

Abstract: Summary Clustering‐based optimal cluster head selection in wireless sensor networks (WSNs) is considered as the efficient technique essential for improving the network lifetime. But enforcing optimal cluster head selection based on energy stabilization, reduced delay, and minimized distance between sensor nodes always remain a crucial challenge for prolonging the network lifetime in WSNs. In this paper, a hybrid elephant herding optimization and cultural algorithm for optimal cluster head selection (HEHO‐CA‐OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Simulation outcomes demonstrated that the proposed algorithm greatly surpassed the existing solutions' performance in noisy environments and encouraged further improvement and testing of the metaheuristic methods. For the network lifespan's extension, a proposal for a hybrid elephant herding optimization and cultural algorithm for optimal cluster head selection (HEHO-CA-OCHS) scheme was given in Murugadass et al [15]. The proposed scheme utilized the belief space's merits, framed by the cultural algorithm for defining a separating operator that was potent for constructing new local optimal solutions within the search space.…”
Section: Related Workmentioning
confidence: 99%
“…Simulation outcomes demonstrated that the proposed algorithm greatly surpassed the existing solutions' performance in noisy environments and encouraged further improvement and testing of the metaheuristic methods. For the network lifespan's extension, a proposal for a hybrid elephant herding optimization and cultural algorithm for optimal cluster head selection (HEHO-CA-OCHS) scheme was given in Murugadass et al [15]. The proposed scheme utilized the belief space's merits, framed by the cultural algorithm for defining a separating operator that was potent for constructing new local optimal solutions within the search space.…”
Section: Related Workmentioning
confidence: 99%
“…However, this CH selection approach struggles extensively in the process of handling the scalability issues. An integrated elephant herd optimization and cultural algorithm (EHOCA)-based CH selection scheme is proposed by Murugadass and Sivakumar 22 for prolonging the network lifetime with maximized energy stability. This EHOCA approach includes the advantages of belief space for a suitable definition of separating operator that aids in optimal balance between diversification and intensification.…”
Section: Intelligent Metaheuristic Optimization Algorithm-based Ch Selection Schemesmentioning
confidence: 99%
“…This ABOA is identified to be predominantly based on the different sets of evaluation conducted using benchmarked functions. 22 However, they exhibit some limitations when they are employed in the real-life engineering optimization problems such as CH selection that focus on network lifetime enhancement in WSNs. Moreover, the standard ABOA variants are identified to be incapable of determining the global optimal solution.…”
Section: Modified African Buffalo and Group Teaching Optimization Algorithm (Mabgtoa) For Cluster Head Selectionmentioning
confidence: 99%
“…14 But this work mainly concentrates on the development of hybrid swarm intelligent clustering approaches with load balancing for achieving heterogeneous arbitrary deployment, which minimizes the energy consumption and increases network lifetime. 15 Moreover, the proposed schemes considered load balancing and heterogeneity as the two eyes during clustering for improving the network efficiency. It adopted a load balancing-imposed clustering mechanism for constructing the clusters in such a way that only minimized load is imposed over the clusters that are constructed near to the BS.…”
Section: Introductionmentioning
confidence: 99%
“…The main motivation of this proposed work, nevertheless, focusses on the improvement of energy efficiency in the network 14 . But this work mainly concentrates on the development of hybrid swarm intelligent clustering approaches with load balancing for achieving heterogeneous arbitrary deployment, which minimizes the energy consumption and increases network lifetime 15 . Moreover, the proposed schemes considered load balancing and heterogeneity as the two eyes during clustering for improving the network efficiency.…”
Section: Introductionmentioning
confidence: 99%